2003
DOI: 10.1023/b:caco.0000007962.19066.9c
|View full text |Cite
|
Sign up to set email alerts
|

Occupation and bladder cancer among men in Western Europe

Abstract: Metal workers, machinists, transport equipment operators and miners are among the major occupations contributing to occupational bladder cancer in men in Western Europe. In this population one in 10 to one in 20 cancers of the bladder can be attributed to occupation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
171
2
7

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 219 publications
(191 citation statements)
references
References 28 publications
11
171
2
7
Order By: Relevance
“…An in vitro investigation carried out by Wolf et al (Wolf et al, 2005) found that cells treated with benzo [a] pyrene showed a dramatic increase in the expression of CYP1A1. Similar conclusions were also found in other experimental animals whose bladder cells were exposed to tobacco containing compounds such as benzo[a]pyrene and arylamines (Kogevinas et al, 2003;Dorrenhaus et al, 2007). However, we failed to reveal any evidence of an association between the two CYP1A1 polymorphisms and BC susceptibility overall, regardless of the additive, dominant, or recessive genetic models.…”
Section: Discussionsupporting
confidence: 89%
“…An in vitro investigation carried out by Wolf et al (Wolf et al, 2005) found that cells treated with benzo [a] pyrene showed a dramatic increase in the expression of CYP1A1. Similar conclusions were also found in other experimental animals whose bladder cells were exposed to tobacco containing compounds such as benzo[a]pyrene and arylamines (Kogevinas et al, 2003;Dorrenhaus et al, 2007). However, we failed to reveal any evidence of an association between the two CYP1A1 polymorphisms and BC susceptibility overall, regardless of the additive, dominant, or recessive genetic models.…”
Section: Discussionsupporting
confidence: 89%
“…Occupational exposure to the following chemical agents is associated with an increased risk of bladder cancer: aromatic amines, paints and solvents, dyes, leather dust, polycyclic aromatic hydrocarbons (PAH), motor exhaust, and chlorinated hydrocarbons (1,(5)(6)(7)(8). Further epidemiologic research is required for many other potential bladder carcinogens.…”
mentioning
confidence: 99%
“…The two established risk factors for TCC are chemical carcinogens from cigarette smoking and occupation exposure (Zeegers et al, 2000;Kogevinas et al, 2003). Bulky DNA adducts formed by these carcinogens are repaired by nucleotide excision repair (NER).…”
mentioning
confidence: 99%